EVALUASI PERENCANAAN PEMECAH GELOMBANG PELABUHAN PERIKANAN TANJUNG ADIKARTA - , irnovia berliana pakpahan, S.T ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Glagah coast have several problems that needs to be solved immediately, such as the instability and short length of the breakwater, engender the gate and flowing into the port occurs to a heavy sedimentation. The purpose of this research is to evaluate the breakwater design of east and west side of Glagah coast, to provide a protection to the pool anchors and sailing plot from the waves strike and also to lower sedimentation rate. In this research, secondary data from previous study is used. Data that used to review jetty in the location are hydro-oceanography data, bathymetry/topography data and existing data, where all data are used in design. Design consists of number of sediment transport through the annual coast (Q) by analytical, graphical method and coastal engineering method (CEM 2000), breakwater length (L), proposed waves height design (HD), crest elevation of breakwater, armor stone weight (W), crest width (B), armor layer stone thickness (t), and stability of armor stone. According to the results of volume discharge (Q) by analytical method, sediment transport (Q) to west side = 1,040,915.36 m3/year, and sediment transport (Q) to east side = 761,476.58 m3/year. By graphical method, sediment transport (Q) to west side =1,054,325.12 m3/year, and sediment transport (Q) to east side = 766,696.88 m3/year. And by CEM 2000 (Coastal Engineering Manual) sediment transport (Q) to west side = 1,153,586.88 m3/year and sediment transport (Q) to east side = 730,373.76 m3/year. After reviewing again, west side breakwater length (L) becomes 345 m (in depth -12) and east side becomes 367 m (in depth -14). Proposed waves height design used in this computation is HD =5.44 m